Perancangan Aplikasi Pendaftaran Pasien Rawat Jalan pada Puskesmas XYZ Berbasis Android - Zulfi Karman; Nurhayati Nurhayati; Manja Purnasari (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
The XYZ Health Center faces challenges in managing the outpatient registration process manually, often resulting in long queues, extended waiting times, and data inaccuracies. To address these issues, this study aims to design and develop an Android-based outpatient registration application. The application is intended to simplify the registration process for patients, allowing them to register for visits without needing to visit the health center in person, while also enabling healthcare staff to manage patient data more efficiently. The methodology employed in this study includes requirements analysis and system design using the Unified Modeling Language (UML). The application features online registration, doctor schedules, visit reminder notifications, and patient data management. This study concludes that the Android-based application can serve as an effective and efficient solution for improving health center services. Further development is recommended to enable integration with other healthcare systems.